The Dynamics of Gender Equality Minangkabau Cultural Perspective and Its Implications for Counseling - Silvianetri, Silvianetri; Irman, Irman (AGENDA: Jurnal Analisis Gender dan Agama, 2022)
Gender equality is a problem that often occurs globally, nationally and locally. This study aims to reveal data related to the dynamics of gender equality from the perspective of Minangkabau culture and its implications for counseling. The research uses a qualitative approach with respondents from all walks of life, especially ninik mamak, cadiak pandai, religious scholars, bundo kanduang and counselor. The data collection techniques in this study are interviews and observation. The research steps are: 1) data collecting, 2) data reduction, 3) data display, and 4) conlusion. To maintain the validity of the data, data triangulation was carried out, especially triangulation of respondents. The results of the research reveal that according to customary law women have gender equality with men in the Minang Realm, but in reality there is still a lot of violence against women. The violence is; sexual violence, physical violence, sychological violence and economic violence. The problem of gender equality is handled by competent experts. One of them is a counselor. The counseling formats used are individual, group and classical formats   The results of this study are expected to be initial data for future researchers who have an interest in researching gender equality.